Strategi Ketahanan Keluarga Petani Kopi Disaat Pandemi Covid-19 di Indonesia - Thiora Pragustia Akhdani; Ade Yunita Mafruhat (Bandung Conference Series: Economics Studies, 2023)
Abstract. This research was conducted to find out what strategies to do to deal with the Covid-19 pandemic. The object of this research is coffee farmers in Indonesia. The method used is literature study and secondary data obtained from the Central Bureau of Statistics (BPS). Family resilience reflects the adequacy and continuity of a family's access to income and resources in order to be able to meet their basic needs, such as food, clean water, health services, education, housing, participation in society, and social integration. The concept of family economic resilience relates to income to meet various needs such as: (1) Food (2) Clean water (3) Health Services (4) Educational Opportunities (5) Houses/Dwellings (Family Resilience Development Indicators 2016) With this article, it is hoped that it will be able to help farmers in dealing with current problems by being able to survive and be able to increase their income in the midst of the Covid-19 pandemic as it is now. Abstrak Penelitian ini dilakukan untuk mengetahui strategi apa yang harus dilakukan untuk menghadapi pandemi covid-19. Objek penelitian ini adalah petani kopi di Indonesia Metode yang digunakan yaitu studi literatur dan data sekunder yang diperoleh dari Badan Pusat Statistik (BPS). Ketahanan keluarga mencerminkan kecukupan dan kesinambungan akses suatu keluarga terhadap pendapatan dan sumber daya agar mampu memenuhi kebutuhan dasarnya, seperti pangan, air bersih, pelayanan kesehatan, pendidikan, perumahan, partisipasi di dalam masyarakat, dan integrasi sosial. Konsep Ketahanan ekonomi keluarga, berhubungan satu sama lain terhadap pendapatan untuk mencukupi beragam kebutuhan seperti : (1) Pangan (2) Air bersih (3) Pelayanan Kesehatan (4) Kesempatan Pendidikan (5) Rumah/ Tempat tinggal (Indikator Pembangunan Ketahanan Keluarga 2016) Dengan adanya tulisan ini diharapkan mampu membantu para petani dalam menghadapi permasalahan saat ini dengan mampu bertahan dan mampu meningkatkan penghasilan ditengah masa pandemi covid-19 seperti sekarang.